USE OF MAPPING IN THE PUBLIC SECTOR: GEOPROCESSING AS DECISION MAKING - Souza, Gustavo de Oliveira Coelho (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2014)
The dismantling of the production of spatial information that occurred in Brazil since the early 1970s, reflects a policy in which the spatial dimension stops making sense in decision -making in public policy. With the advent of neoliberal policies, the process of spatial planning shall be the market responsibility, which will choose according to your logic where to invest. However, whether the market will resent the lack of spatial information for their decisions. In response to this, shall contract mapping services, following their interests. With the resumption of the role of the state in the management of space and public policy, it was evident the great cartographic product liability and dependence only on the market, restricting their use and had dubious quality. As a result, public institutions shall organize teams that are responsible not only for the production of spatial analysis, but also to cartographic production, causing overlap of work and waste of public resources. Attempts are made to organize this situation by sharing of cartographic products among State institutions. Under this scenario exemplifies Seade Foundation’s cartographic production.